DEM-bond model: A computational framework for designing mechanically enhanced polymer nanosphere-based ordered nanostructures - Dan Chen; Zhiren Chen; Tengfang Zhang; Zhihong Zhu; Qingwei Zhou; Fang Luo; Fan Wu; Yunming Wang; Chucai Guo (Materials & Design)
Polymer nanosphere-based devices demonstrate exceptional optoelectronic properties due to the surface and size effect. However, the lack of predictive computational models for nanosphere interactions during fabrication, coupled with inherently weak mechanical strength (<2 MPa) in self-assembled systems, severely limits their industrial applications. To address these challenges, we develop a Discrete Element Method with integrated bond mechanics and hysteretic spring contact models (DEM-Bond) that enables precise computational design of ordered nanostructures. This multi-scale framework uniquely captures critical nanosphere behaviors including bond formation dynamics, plastic deformation, and fracture mechanics during thermoforming processes. Our simulations reveal how interfacial bonding parameters govern macroscopic mechanical performance, demonstrating enhancement in hardness through optimized crosslinking strategies. The model shows remarkable consistency (<5 % deviation) with nanoindentation tests in predicting load–displacement behavior and stress distribution patterns. By establishing quantitative correlations between processing parameters (temperature, pressure, types of crosslinking agents and concentration) and mechanical outputs (stiffness and hardness), the DEM-Bond framework provides a powerful computational platform for rational design of nanostructured polymer devices. This approach demonstrates significant potential for extension to other nanosphere systems including polystyrene and biopolymers, opening new avenues for developing mechanically robust functional nanomaterials.